Experimental study and numerical simulation of precast segmental bridge columns with semi-rigid connections. (1st April 2017) - Hung, Hsiao-Hui; Sung, Yu-Chi; Lin, Kuan-Chen; Jiang, Chi-Rung; Chang, Kuo-Chun
Highlights: A precast segmental bridge pier with small axial prestressing forces was proposed. Two types of connection between each precast element were proposed and tested. Stable ductility behavior and the constructability of the columns were confirmed. Two analysis models of the test configurations were developed. Abstract: To prevent the large axial prestressing forces that are typically necessary for a post-tensioned precast segmental column, a semi-rigid connection for a precast segmental bridge pier system is proposed. The proposed connection between segments is a hybrid connection containing bonded bar reinforcement that is spliced by bar couplers and shear keys to provide shear resistance between neighboring segments. Unbounded tendons with a small prestressing force can also be included to provide re-centering forces. Two types of connection between each prefabricated element, i.e., a steel dowel shear key and a reinforced concrete (RC) shear key, are proposed and tested. From the experimental results and construction practices of the developed system, the high seismic resistance and the satisfactory constructability of the proposed pier are confirmed. Furthermore, to establish a proper analysis procedure for such a bridge column system, two finite-element models using solid elements and beam elements from the laboratory tests are also generated and both are shown to be appropriate and effective in capturing the seismic behavior of the proposed system.